2016
DOI: 10.5194/acp-2015-949
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stratosphere-troposphere exchange in the vicinity of a tropopause fold

Abstract: Transport of air masses from the stratosphere to the troposphere along tropopause folds can lead to peaked ozone concentrations at ground level and hereby influence the long-term trend of tropospheric ozone. To improve the understanding of responsible processes and preferred regions of exchange, transient and reversible exchange processes in the vicinity of a tropopause fold are analysed on the basis of a case study. The global and regional atmospheric chemistry model system MECO(n), which couples the limited-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Even though the influence of the model and emission inventory resolutions on simulated ozone mixing ratios is well known (e.g. Wild and Prather, 2006;Tie et al, 2010;Holmes et al, 2014;and Markakis et al, 2015), the impact of the third factor -the model and emission inventory resolutions -on the simulated contributions of specific emission sources to ozone has not yet been systematically investigated in detail. It is important to investigate this third factor, as source apportionment studies focusing on climate usually use rather coarsely resolved global climate models (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the influence of the model and emission inventory resolutions on simulated ozone mixing ratios is well known (e.g. Wild and Prather, 2006;Tie et al, 2010;Holmes et al, 2014;and Markakis et al, 2015), the impact of the third factor -the model and emission inventory resolutions -on the simulated contributions of specific emission sources to ozone has not yet been systematically investigated in detail. It is important to investigate this third factor, as source apportionment studies focusing on climate usually use rather coarsely resolved global climate models (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This second ozone peak causes a sharp increase in the ozone concentration in the vicinity of the tropopause, which not only increases the total ozone [14], but also often affects the surface ozone concentration [20]. Recent studies have shown that the STE is accelerating due to climate change [14][15][16][17][18][19], the direct cause of which is reported to be the increased blocking of synoptic waves due to global warming [15,17,21,22]. The concentration of tropospheric ozone also shows an obvious increasing trend caused by various factors, such as an increase in precursors, transport of ozone from surrounding areas, and changes in regional climate characteristics [2, 15,23].…”
Section: Introductionmentioning
confidence: 99%
“…This observational evidence is mainly based on in situ aircraft measurements (e.g. Esler et al, 2003;Homeyer et al, 2011), on airborne and ground-based lidar observations (e.g. Browell et al, 1987;Langford et al, 2009;Trickl et al, 2010), and on ozone and water vapour sondes (e.g.…”
Section: Introductionmentioning
confidence: 99%